A scientific explanation and understanding of epistemological issues in tourism research (a study based on the theories of Kurt Lewin and John Tribe) - Alejziak, Wiesław (Turyzm/Tourism, 2019)
The article presents the essence as well as various models of academic explanation and the explanatory value of understanding, indicating their usability and limitations as regards understanding why and how tourism functions. Particular attention has been paid to the epistemological dimension of tourism research, as well as its new directions. The author has referred to two models concerning the epistemological aspects of tourism research where the focal point is the category of ‘truth about tourism’. These have been presented in two articles by John Tribe.